PELATIHAN MANAJEMEN FINANSIAL UMKMUNTUK MENDUKUNG KOMPETENSI KEWIRAUSAHAANSISWA SISWI PESANTREN UMMUL QURA - Lisdawati Lisdawati; Akhmad Akbar; Eko Cahyadi (LAP4B, 2026)
Developing entrepreneurial spirit among pesantren students is an important need to prepare them to face future economic challenges while maintaining Islamic values in business. This Community Service Program aims to improve the entrepreneurial competence of Pesantren Ummul Qura students through comprehensive and applicable MSME financial management training. The activity was conducted on March 7-9, 2026 using interactive learning methods that combine lectures, practical workshops, successful MSME case studies, and sharia-based business financial management simulations. Program participants were 42 santri who have interest and plans to become entrepreneurs after completing their education at the pesantren. Evaluation results showed a significant increase in financial management understanding with average pre-test scores of 61.5 increasing to 83.7 on post-test, indicating a 36% improvement in material mastery. Practical skills assessment through business simulation showed 86% of participants were able to prepare simple financial plans for small businesses correctly. Satisfaction survey showed 91% of participants rated the program as very beneficial and 88% felt more confident to start their own business. This program proves that structured and contextual financial management training can effectively equip santri with solid entrepreneurial competencies that are in accordance with Islamic values.